Pengaruh Store Atmosphere, Harga, Variasi Menu Terhadap Minat Kunjungan Konsumen Studi Kasus: Cafeetory Café Denpasar - Ratnasari, Dewik; Wirati Adriati, I Gst. Ayu (Masyarakat Ekonomi Syariah Bogor, 2025)
The development of the cafe industry in Bali shows increasingly fierce competition, encouraging businesses such as Cafeetory Café to continue to innovate in creating an engaging experience for consumers. The instability of revenue experienced by Cafeetory Café reflects the importance of understanding factors such as store atmosphere, price, and menu variety that can influence visit interest. Based on this phenomenon and the results of previous studies that showed mixed findings, this study was conducted to analyze the influence of these three factors on consumer visit interest at Cafeetory Café Denpasar. This study used a quantitative method by distributing questionnaires to 102 respondents with the criteria of knowing Cafeetory Café through social media and having an Instagram account. The instruments tested were validity and reliability tests, followed by classical assumption tests and multiple linear regression. In conclusion, store atmosphere has a positive and significant effect on the interest in visiting Cafeetory Café, price has a positive and significant effect on the interest in visiting Cafeetory Café, menu variety has a positive and significant effect on the interest in visiting Cafeetory Café, and store atmosphere, price, and menu variety together have a positive and significant effect on the interest in visiting Cafeetory Café. Cafeetory Café is advised to maintain the quality of the cafe atmosphere through comfort, layout, lighting, and cleanliness to strengthen the positive image and consumer experience. Competitive pricing strategies that are comparable to product quality and regular promotions need to be implemented to attract and retain customers. In addition, menu innovation according to trends and further research with more diverse variables and methods are recommended to enrich the understanding of consumer behavior.